2015
DOI: 10.1103/physrevb.92.201408
|View full text |Cite
|
Sign up to set email alerts
|

Landau quantization and Fermi velocity renormalization in twisted graphene bilayers

Abstract: Currently there is a lively discussion concerning Fermi velocity renormalization in twisted bilayers and several contradicted experimental results are reported.Here we study electronic structures of the twisted bilayers by scanning tunneling microscopy (STM) and spectroscopy (STS). The interlayer coupling strengths between the adjacent bilayers are measured according to energy separations of two pronounced low-energy van Hove singularities (VHSs) in the STS spectra.We demonstrate that there is a large range of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
81
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 30 publications
14
81
0
4
Order By: Relevance
“…In particular, it has been theoretically suggested that the twist in the BLG may lead to a renormalization of the Fermi velocity [17], possible appearance of the flat electronic bands [18], neutrino-like oscillation of Dirac fermions [19] as well as localization of electrons [20]. Moreover, TBLG when placed in a magnetic field, exhibits a fractal spectrum of the Landau levels [21].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been theoretically suggested that the twist in the BLG may lead to a renormalization of the Fermi velocity [17], possible appearance of the flat electronic bands [18], neutrino-like oscillation of Dirac fermions [19] as well as localization of electrons [20]. Moreover, TBLG when placed in a magnetic field, exhibits a fractal spectrum of the Landau levels [21].…”
Section: Introductionmentioning
confidence: 99%
“…3a. Consequently, it is expected to observe Landau quantization of massless Dirac fermions in twisted bilayers with larger rotation angles 16,28 . This is demonstrated explicitly in our experiment, where the observed Landau levels sequence in the 3.1° bilayer, as shown in Fig.…”
mentioning
confidence: 99%
“…• ), the twisted bilayers behave as two decoupled single-layer graphene sheets with a Fermi velocity of v F ≈ 1.1 × 10 6 m/s [181,182]. At a small rotation angle (θ < 6…”
Section: Twisted Bilayersmentioning
confidence: 99%
“…• ), the electronic states near the Dirac cones of two layers couple with a reduced interlayer hopping amplitude of t θ ≈ 0.4t ⊥ (t ⊥ is the interlayer hopping for AB-stacked layers) [179,182,193]. As a result, the two Dirac cones intersect and hybridize at the energy of ± v F ∆K, generating two saddle points in the energy bands [ Fig.…”
Section: Twisted Bilayersmentioning
confidence: 99%